IMPROVING THE MECHANISM OF REDUCING FINANCIAL RISKS OF INNOVATIVE ACTIVITIES IN TEXTILE ENTERPRISES - Rashidov Jamshid (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
The dynamic development of Uzbekistan’s textile industry, accounting for over 60% of the country’s non-commodity exports in 2024, demands new mechanisms to mitigate financial risks associated with innovation. This study identifies the primary financial vulnerabilities faced by innovative textile enterprises, such as credit risk, cash flow volatility, and innovation investment uncertainty. Through comparative analysis, the paper proposes a multi-layered mechanism incorporating financial hedging instruments, innovation insurance models, and government-backed risk-sharing schemes. Empirical data from 130 Uzbek textile firms highlight that adopting structured financial risk management systems could reduce financial losses by up to 18% annually. The findings serve as a theoretical and practical guide to enhancing financial sustainability in the context of Uzbekistan’s ongoing industrial modernization.